THE MAIN FEATURES OF THE PRIMARY SCHOOL TEACHER'S COMPETENCE IN ESTABLISHING COOPERATIVE RELATIONS WITH STUDENTS' FAMILIES - Khamidova Barno Makhmudovna (Journals Park Publishing, 2022)
In this work, the main features of the competency of future elementary education teachers to establish cooperative relationships with students' families are discussed.
Keywords: primary school teacher, competence, cooperation with families, communicative competence.